A right inguinoscrotal swelling: the importance of histological analysis. (7th September 2012) - Patrick, Nina; Iskander, Morkos; Brougham, Katherine; McCabe, John
Abstract : Myxofibrosarcoma of the spermatic cord is a rare condition. We present an unusual case of a 69-year-old gentleman who presented to the emergency department on two occasions with a right inguinoscrotal swelling. We will explore the diagnostic difficulties encountered and subsequent management. We will also highlight the importance of histological analysis when unexpected findings are encountered.